2010
DOI: 10.1029/2009jb006569
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the seismogenic zone in the epicentral region of the 26 December 2004 great Sumatra‐Andaman earthquake: Results from seismic refraction and wide‐angle reflection surveys and thermal modeling

Abstract: [1] The 26 December 2004 Sumatra earthquake (M w = 9.1) initiated around 30 km depth and ruptured 1300 km of the Indo-Australian -Sunda plate boundary. During the Sumatra-OBS (ocean bottom seismometer) survey, a wide-angle seismic profile was acquired across the epicentral region. A seismic velocity model was obtained from combined travel time tomography and forward modeling. Together with reflection seismic data from the SeaCause II cruise, the deep structure of the source region of the great earthquake is re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 106 publications
9
65
0
Order By: Relevance
“…This correlation is generally understood in terms of a change in frictional properties along the fault, either the brittle-ductile transition or the intersection of the subduction thrust with hydrated mantle (Hyndman et al, 1997;Peacock and Hyndman, 1999). However earthquakes that extend below the shallow mantle wedge at Sumatra, northeastern Japan, and the Mariana trench are leading to challenges of this view (Dessa et al, 2009;Emry et al, 2011;Heuret et al, 2011;Hino et al, 2000;Klingelhoefer et al, 2010;Simoes et al, 2004). The updip extent of observed seismicity appears well correlated with temperatures along the subduction thrust between 100°and 150°C (Hyndman andWang, 1993, 1995;Hyndman et al, 1997;Oleskevich et al, 1999).…”
Section: Introductionmentioning
confidence: 81%
“…This correlation is generally understood in terms of a change in frictional properties along the fault, either the brittle-ductile transition or the intersection of the subduction thrust with hydrated mantle (Hyndman et al, 1997;Peacock and Hyndman, 1999). However earthquakes that extend below the shallow mantle wedge at Sumatra, northeastern Japan, and the Mariana trench are leading to challenges of this view (Dessa et al, 2009;Emry et al, 2011;Heuret et al, 2011;Hino et al, 2000;Klingelhoefer et al, 2010;Simoes et al, 2004). The updip extent of observed seismicity appears well correlated with temperatures along the subduction thrust between 100°and 150°C (Hyndman andWang, 1993, 1995;Hyndman et al, 1997;Oleskevich et al, 1999).…”
Section: Introductionmentioning
confidence: 81%
“…6a, the observation of surface deformation in this area is strong evidence in support of the notion that there was localized coseismic deformation in the area of the proposed splay fault during the 2004 earthquake. KLINGELHOEFER et al (2010) observed many landward and seaward vergent faults in the accretionary prism to the northwest of Salaut Besar. One of these landward vergent structures roughly correlates with the observed surface deformation and may indicate the presence of a family of such faults in the area (MELTZNER et al, 2010).…”
Section: Surface Deformation On Salaut Besar Islandmentioning
confidence: 99%
“…Several studies were conducted in the area north of Simeulue island at 3 • N to 4 • N using MCS and wide-angle seismic studies Dessa et al, 2009;Klingelhoefer et al, 2010) as well as gravity and thermal modelling (Klingelhoefer et al, 2010). All of them obtain similar depths for the updip limit of the SZ in that region.…”
Section: Off Sumatra From North To Southmentioning
confidence: 99%